Normal Cerebral Oxygen Consumption Despite Elevated Cerebral Blood Flow in Adolescents With Bipolar Disorder: Putative Neuroimaging Evidence of Anomalous Energy Metabolism - Karthikeyan, Sudhir; Fiksenbaum, Lisa; Grigorian, Anahit; Lu, Hanzhang; MacIntosh, Bradley J.; Goldstein, Benjamin I. (Frontiers in Psychiatry, 2019)
Background: Regional cerebral blood flow (CBF) is reportedly altered in both adolescents and adults with bipolar disorder (BD). Whether these CBF differences are part of an overall imbalance in cerebral energy homeostasis remains unknown. Therefore, we examined global cerebral metabolic rate of oxygen consumption (CMRO2) as a physiological index of brain metabolism in adolescents with and without BD. Methods: 115 adolescents (mean age 17.3 ± 1.4 years), including 58 BD (type I, II or NOS) and 57 age-matched healthy controls (HC) participated in this Magnetic Resonance Imaging (MRI) study. Global estimates for venous blood oxygenation (Yv) and grey matter CBF were measured using T2-relaxation-under-spin-tagging (TRUST) and arterial spin labeling (ASL) MRI, respectively. CMRO2 was calculated using the Fick principle of arteriovenous difference to test for a group difference. We also examined CMRO2 in relation to mood states (i.e. euthymic, depressed, or hypomanic/mixed). Results: Although CBF was significantly higher in BD compared to HC, there was no group difference in global CMRO2, nor Yv. Meanwhile, Yv significantly decreased with age and females tended to have greater CBF and CMRO2 in comparison to males. Lastly, there was no significant association between CMRO2 and mood states. Conclusions: Our results indicate a potential mismatch between cerebral blood supply and oxygen metabolism in BD, suggesting inefficiency in energy homeostasis in the brain. Mapping CMRO2 would provide the spatial resolution to investigate regional alterations in metabolism, particularly in the brain regions where CBF is increased.